Long-term use of pegylated liposomal doxorubicin to a cumulative dose of 4600 mg/m2 in recurrent ovarian cancer. Issue 7 (August 2017) - Pendlebury, Adam; DeBernardo, Robert; Rose, Peter G.
Abstract : Pegylated liposomal doxorubicin (PLD) is used widely in gynecologic oncology and other oncology disciplines. Native doxorubicin use is associated with the potential for significant toxicity. Cardiac toxicity in particular limits lifetime dose. PLD has not been shown to be associated with clinical cardiac toxicity. We report on the long-term use of PLD in a patient with recurrent high-grade serous ovarian cancer to a lifetime dose of 4600 mg/m 2 . This therapy was associated with long-term stable disease, good performance status, and minimal adverse effects.